Are female athlete specific health considerations being assessed and addressed in preparticipation examinations? A scoping review and proposed framework - Schulz, J. M.; Pohlod, L.; Myers, S.; Chung, J.; Thornton, J. S. (Journal of Sport and Health Science, 2025)
Background Preparticipation examinations (PPEs) are unstandardized screening tools routinely used to collect an athlete's baseline health information prior to the start of a new competitive season. However, many PPEs include minimal and often nonspecific questions related to the health concerns of female athletes. A lack of female athlete specific health questions could result in missed red flags and subsequent injury or illness. As such, the objectives of this scoping review were to (a) determine what female athlete specific health questions currently exist in PPEs in the scientific literature to prevent injury and illness, and (b) map the results against the health domains outlined in the International Olympic Committee (IOC) consensus statement supplement on the female athlete. Methods We searched Embase, Scopus, CINAHL, Medline Ovid, and SPORTDiscus from inception to December 2022. Any study with female athlete specific health PPE questions or recommendations for questions (i.e., menstrual health, eating habits, musculoskeletal health, etc.) was included. Three reviewers independently screened titles and abstracts, followed by full text articles for eligibility and data extraction, with conflicts resolved by a third-party reviewer. Extracted data were summarized into 3 determined groupings. Results Of the 1356 studies screened, 41 were included in this study. Forty studies (98%) included questions/recommendations related to menstrual health. Thirty-one studies (76%) had questions/recommendations concerning disordered eating/eating habits. Twenty-four studies (59%) referred to body weight/image, and 16 studies (39%) referred to musculoskeletal health. No studies included questions on all IOC female athlete health domains. Conclusion There is currently a gap in female athlete specific health content included in PPEs. A more comprehensive, standardized PPE with a focus on inclusion of female athlete specific health questions and considerations should be developed to improve health and optimal participation of female athletes around the world.